PASTEURIZATION OF COCONUT WATER AND RICE WASHING WATER AS A SUPPLEMENT FOR EXTENDING THE LIFE OF OYSTER MUSHROOM CULTIVATION MEDIA - Febriana Alfianti; Sutarman Sutarman; Afifati Cahya Murti; Muhammad Burhanuddin Adenan (Universitas Muhammadiyah Purwokerto, 2021)
This study aims to determine the potential effect of pasteurization on the resistance of coconut water and cherry water as a nutritional supplement in the cultivation of oyster mushrooms (Pluerotus ostreatus) and to obtain information on the temperature range and duration of the pasteurization process which can increase nutrient resistance in rice washing water and coconut water so that it can be obtained. the potential use of it is known to extend the life of baglog in oyster mushroom cultivation. This research was conducted from May to October 2020 using the method of review and in-depth literature review. The results showed that the addition of nutrient water and coconut water to the baglog medium had no effect on the number of fruit bodies per clump, the diameter of the fruit caps, the length of the fruit hood stalks, the fruit body weight, and the fruit body weight/baglog of white oyster mushroom (P. ostreatus). Heating 80oC for 20 minutes against rice washingwater and heating 80oC for 20 minutes for coconut water has the potential to increase the life of the baglog because it can extend the resistance of the supplement material from premature destruction of indigenous contaminant microbes and environmental physical factors.